Considerations for the design of overdose education and naloxone distribution interventions: results of a multi-stakeholder workshop - Kate Sellen; Benjamin Markowitz; Janet A. Parsons; Pamela Leece; Curtis Handford; Nick Goso; Shaun Hopkins; Michelle Klaiman; Rita Shahin; Geoffrey Milos; Amy Wright; Mercy Charles; et al. (BMC, 2023)
Abstract Introduction Opioid overdose epidemic is a public health crisis that is impacting communities around the world. Overdose education and naloxone distribution programs equip and train lay people to respond in the event of an overdose. We aimed to understand factors to consider for the design of naloxone distribution programs in point-of-care settings from the point of view of community stakeholders. Methods We hosted a multi-stakeholder co-design workshop to elicit suggestions for a naloxone distribution program. We recruited people with lived experience of opioid overdose, community representatives, and other stakeholders from family practice, emergency medicine, addictions medicine, and public health to participate in a full-day facilitated co-design discussion wherein large and small group discussions were audio-recorded, transcribed and analysed using thematic approaches. Results A total of twenty-four participants participated in the multi-stakeholder workshop from five stakeholder groups including geographic and setting diversity. Collaborative dialogue and shared storytelling revealed seven considerations for the design of naloxone distribution programs specific to training needs and the provision of naloxone, these are: recognizing overdose, how much naloxone, impact of stigma, legal risk of responding, position as conventional first aid, friends and family as responders, support to call 911. Conclusion To create an naloxone distribution program in emergency departments, family practice and substance use treatment services, stigma is a central design consideration for training and naloxone kits. Design choices that reference the iconography, type, and form of materials associated with first aid have the potential to satisfy the need to de-stigmatize overdose response.